Are College Costs Worth It? How Individual Ability, Major Choice, and Debt Affect Optimal Schooling Decisions - Douglas A. Webber (Institute for the Study of Labor (IZA), 2015)
This paper examines the financial value over the course of a lifetime of pursuing a college degree under a variety of different settings (e.g. major, student loan debt, individual ability). Using a lifecycle simulation approach, I account for ability/selection bias and the substantial probability that entering college freshmen will not eventually graduate, two critically important factors when evaluating the value of pursuing a college degree. I find that financial proposition of attending college is an unambiguously good investment for the vast majority of individuals with low to average college costs, although majors with a lower expected return do not pay off until middle age. However, when the financial costs of attending college are high (defined here as roughly 30,000 per year), the gains from attending college are far more tenuous, particularly among those with below median ability and those pursuing an Arts/Humanities degree. I estimate the net present discounted value of attending college to vary between 95,000 and 275,000 depending on the major (STEM, Business, Social Sciences, Arts/Humanities) pursued.
Keywords: I21; I22; I23; 330; student loans; returns to college; major choice